Endotracheal Intubation With and Without Night Vision Goggles in a Helicopter and Emergency Room Setting: A Manikin Study. Issue 9 (1st September 2015) - Gellerfors, Mikael; Svensén, Christer; Linde, Joacim; Lossius, Hans Morten; Gryth, Dan
ABSTRACT: Background: Securing the airway by endotracheal intubation (ETI) is a key issue in prehospital critical care. Night vision goggles (NVG) are used by personnel operating in low-light environments. We examined the feasibility of an anesthesiologist performed ETI using NVG in a helicopter setting. Methods: Twelve anesthesiologists performed ETI on a manikin in an emergency room (ER) setting and two helicopter settings, with randomization to either rotary wing daylight (RW-D) or rotary wing in total darkness using binocular NVG (RW-NVG). Primary endpoint was intubation time. Secondary endpoints included success rate, Cormack–Lehane (CL) score, and subjective difficulty according to the Visual Analoge Scale (VAS). Results: The median intubation time was shorter for the RW-D compared to the RW-NVG setting (16.5 seconds vs. 30.0 seconds; p = 0, 03). We found no difference in median intubation time for the ER and RW-D settings (16.8 seconds vs. 16.5 seconds; p = 0.91). For all scenarios, success rate was 100%. CL and VAS varied between the ER setting (CL 1.8, VAS 2.8), RW-D setting (CL 2.0, VAS 3.0), and RW-NVG setting (CL 3.0, VAS 6.5). Conclusion: This study suggests that anesthesiologists successfully and quickly can perform ETI in a helicopter setting both in daylight and in darkness using binocular NVG, but with shorter intubation times in daylight.